School leadership during times of major change - Miller, Mischel Dawn (Kansas State University, 2021)
With this research project, I intended to describe the skills and dispositions needed by school leaders during times of dramatic change. Change is a given; during this study, our world underwent an extraordinary transformation. In March 2020, President Donald Trump announced that our nation was facing an unprecedented pandemic. With this, schools across the country shut their doors to the educational process most of us know and understand. At once, our nation’s educational leaders were faced with teaching students in ways no one would have dreamed could be implemented, let alone in such short order. As fear of the virus dissipated and educational leaders and others began to look at the new delivery model, a new normal began to emerge. With this research, I intended to determine the skills and dispositions needed by school leaders in what has become the most significant and dramatic change in my career as an educator. As a result of the COVID-19 Pandemic, the leaders who participated in this study were dealing with unprecedented concerns related to health and safety. Each of these leaders was passionate about leading student achievement and supporting their staff during this time of uncertainty. However, the harsh reality of the pandemic was schools were dramatically impacted and forced to change their practices to meet the immediate and short-term educational goals, while at the same time dealing with possible life and death situations. It is important to note all participants in this study were part of the Kansas State Department of Education's Redesign Project and had been involved in voluntary change initiatives prior to the research, but the forced change caused by the pandemic, definitely put mental stress on each of the participants due to the pandemic. The results of this study indicated that communication, and culture, which included specifically targeted and timely support, as the primary skills and dispositions needed by leaders during times of dramatic change.
Keywords: School leadership; Rapid educational change; Leadership skills